Alien mammal species in floodplain habitats of the Siversky Donets basin (Ukraine) - Denys Lazariev (Theriologia Ukrainica, 2023)
An analysis of invasions and expansions of mammals in the Siversky Donets basin and adjacent areas is presented. Data on population and range the dynamics of habitats and the number of semi-aquatic mammals of two groups are given. The first group includes alien species that were introduced and had previously been unknown in the fauna of not only the region, but also Ukraine in general: muskrat (Ondatra zibethicus), coypu (Myocastor coypus), American mink (Neogale vison), and raccoon dog (Nyctereutes procyonoides). The second group includes local invaders, which nowadays are expanding their range, inhabiting the river and its tributaries: Eurasian beaver (Castor fiber) and Eurasian otter (Lutra lutra). The maps presented show the process of animal spread in the region, indicating the places of introduction, directions of expansion, and known registrations. For local invaders, the territory of their natural habitat at the time of the start of acclimatiszation (for Castor fiber) or expansion to steppe regions (for Lutra lutra) is indicated. Population dynamics of all the species considered was analysed using data from the State Statistical Reporting, for the period from 1984 to 2021, and also monitoring data of other investigators for the pre-war period (until February 2022). The results of the statistical analysis show that populations of the the number of introduced species of mammals increases increased rapidly from the time of their appearance in the composition of the fauna, after which their numbers began to decreases. Also, a number of factors were noted that over a certain period of time exerted had an additional influence on the population dynamics of several certain alien mammal species of mammals. Data on long term dynamics of local invaders show that, along with the expansion of animals to new areas and increase in their abundance, a decrease of their numbers in areas of their historical distribution took place, such as in the case of Lutra lutra. Concerning the distribution and abundance of Castor fiber, an ambiguous situation has appeared: the state of its populations in some steppe areas is better than in the forest areas, where its number abundance is decreasing. Information on the distribution and population state of the studied species based on OSINT-analysis, author’s data and questionnaire surveys are presented. The results of introduction of the studied species are discussed.